USE OF TERMINOLOGY AND (META)LINGUISTIC AWARENESS IN GRADE 4 EXPERIENCE FROM A PILOT STUDY - Kovács, Attila Tibor (Tudásmenedzsment, 2024)
To understand the texts we read, we need language use and linguistic knowledge, as well as metalinguistic awareness related to the text. We examined linguistic and metalinguistic awareness in two areas: at the level of compound words and in relation to words with suffixes. We operated with the following assumptions in our action research: H1: The participants achieve better results in tasks related to affixed words. H2: Those who can justify their answers and reflect on their question answering process using grammatical terms will achieve better results in completing the worksheet. The 15-task test measures metalinguistic knowledge related to compound and suffixed words. The solutions require either implicit or explicit elaboration. Out of the 36 utterances in the "interpretative" text, grammatical metalanguage-related expressions were used by the informants in 13 cases. Through the use of quantitative content analysis, the study could contribute to the development of native language methodology and grammar teaching in lower primary education.